(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article describes the characteristics of a tale as an independent genre of literature, its structural, semantic, and stylistic peculiarities. The author gives a brief description of the development and characteristics of Kazakh and English tales, the peculiarities of its perception. The author also makes an attempt to define the main problems and difficulties of translation. The author states that in the process of translating a tale the translator should consider and synthesize linguistic and literary characteristics of the original in order to provide adequate translation. One of the principal difficulties in translation is national cultural adaptation, as the translator has to contrast both languages and different cultures.